Loading on aluminium rivet joint - Muhammad Fikri , Md Naziar (2012)
Joint is combining two or more component for an application. Rivet joint is a method to joint two components in real world. Nowadays, rivet joint commonly used in manufacturing industry, automobile industry and also in aerospace industry due to the good clam-up, lightweight and good in corrosion resistance. This thesis deal with the loading for a group of aluminium AA5052 blind rivet pop with the steel plate AISI1006. This assessment have two objectives which first to investigate the shear stress on a group of aluminium rivet and second to determine whether centroid of joint influence the strength of joint. Six different geometry of riveted joint was design to achieve the objectives. Three from six design were used to design in variable rivet distance from centroid but constant in angle from centroid meanwhile the other three were designs with constant rivet distance from centroid and different in angle from centroid. The experiment was used the Shimadzu Tensile Test Machine for testing the design in axial force. Result obtained from experiment will be compared to the simulation by using Algor Fempro. From the result, the farthest distance rivets from centroid hold the highest load and the centroid influence the strength of joint. The best position will hold the highest load, highest stress and highest shear is at position of rivet 21mm distance from centroid and angle 51°.